Digital in the Bank System of Uzbekistan Financial Services Application Mechanisms - Ruziyev Zafar Ikromovich; Suyunov Dostonbek Rustamovich (Scientific Trends, 2024)
The digitization of the economy poses serious challenges to existing business models, including structural divisions of the banking system, which is currently undergoing a transformation process around the world. Customer focus and personalization of the offer are key components of a digital banking strategy. For its effective implementation, it is necessary to solve tasks focused on the accumulated experience of customers, as well as on the introduction of innovations that support the interests of customers. The article discusses the areas of application of digital technologies in the banking sector of Uzbekistan, as well as in the leading banking structures of the world, the problems and prospects of digitalization of banking business are highlighted.
Keywords: Digital banking, electronic transaction, mobile communication, Internet, neobank, commercial bank, retail bank, traditional bank, digital technologies.